Does implementation of the universal health insurance affect the quality of referral in the healthcare system? A cross-sectional comparative study in Egypt - Nesrine Saad Farrag; Abdel-H; Ateya Megahed Ibrahim; Sherehan Abdelsalam (Wolters Kluwer Medknow Publications, 2021)
Background: The Universal Health Insurance System (UHIS) has currently entered into service in July 2019 in Port-Said, a small governorate in Egypt, as a pilot to be generalized in 5 phases. Objectives: The study aimed to compare the quality of referral practice under the UHIS and the traditional system (Mansoura). Methods: A comparative cross-sectional study that was conducted in the duration from July 2019 to June 2020, targeted all physicians and nurses working in primary health care (PHC) sites and hospitals within the UHIS (204 doctors, 396 nurses) with an equal number from PHC sites and hospitals in Mansoura (205 doctors and 395 nurses). A predesigned validated self-administered questionnaire was used to collect data. Results: The study included 1200 physicians and nurses. Results showed that receiving referrals without letters and referrals not conforming with the rules were significantly lower in the UHIS (13.4% vs. 50.2%, and 39.5% vs. 60.7%, respectively). Denying a referral was significantly higher in the UHIS (38.8% vs. 21%, P ≤ 0.001). The drawbacks in the referral system were less reported in the UHIS (P ≤ 0.001 for most items). There were no significant differences regarding the presence of rules for referral or attending training courses related to the referral process (P = 0.269, P = 0.188, respectively). Conclusions: The study indicates that considerable improvements in the quality of the referral process were achieved. However, the system needs more efforts related to in-service training of the staff, feedback letter.